Fisheries Surveys Are Essential Ocean Observing Programs in a Time of Global Change: A Synthesis of Oceanographic and Ecological Data From U.S. West Coast Fisheries Surveys - Gallo, Natalya D.; Bowlin, Noelle M.; Thompson, Andrew R.; Satterthwaite, Erin V.; Brady, Briana; Semmens, Brice X. (Frontiers in Marine Science, 2022)
As climate change and other anthropogenic impacts on marine ecosystems accelerate in the 21st century, there is an increasing need for sustained ocean time series. A robust and collaborative network of regional monitoring programs can detect early signs of unanticipated changes, provide a more holistic understanding of ecosystem responses, and prompt faster management actions. Fisheries-related surveys that collect fisheries-independent data (hereafter referred to as “fisheries surveys”) are a key pillar of sustainable fisheries management and are ubiquitous in the United States and other countries. From the perspective of ocean observing, fisheries surveys offer three key strengths: (1) they are sustained due to largely consistent funding support from federal and state public sector fisheries agencies, (2) they collect paired physical, chemical, and biological data, and (3) they have large and frequently overlapping spatial footprints that extend into the offshore region. Despite this, information about fisheries survey data collection can remain poorly known to the broader academic and ocean observing communities. During the 2019 CalCOFI Symposium, marking the 70th anniversary of the California Cooperative Oceanic Fisheries Investigations (CalCOFI), representatives from 21 ocean monitoring programs on the North American West Coast came together to share the status of their monitoring programs and examine opportunities to leverage efforts to support regional ecosystem management needs. To increase awareness about collected ocean observing data, we catalog these ongoing ocean time series programs and detail the activities of the nine major federal or state fisheries surveys on the U.S. West Coast. We then present three case studies showing how fisheries survey data contribute to the understanding of emergent ecosystem management challenges: marine heatwaves, ocean acidification, and contaminant spills. Moving forward, increased cross-survey analyses and cooperation can improve regional capacity to address emerging challenges. Fisheries surveys represent a foundational blueprint for ecosystem monitoring. As the international community moves toward a global strategy for ocean observing needs, fisheries survey programs should be included as data contributors.